Giovani e materia 1994 : ricerca e tendenza. - Spadolini, Benedetta; Sogese; Gambone, Bruno ([s.l.] : Sogese, 1994)
58a Mostra Mercato Internazionale dell' Artigianato
Adlib record nr. 530010947
boek
Keywords: Italië